Analysis of heavy metal levels in fish of the Diwaniyah River: Environmental impacts and health risks to humans - Dhafer Hameed Majeed Al Taie; Monia EL Bour (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study examines the presence of heavy metal pollution in three prevalent species of river fish, namely Cyprinus carpio, Spondyliosoma cantharus, and Liza bandialensis Diouf, from the Al-Diwaniyah River. The concentrations of lead (Pb), cadmium (Cd), zinc (Zn), iron (Fe), and copper (Cu) in the muscle tissue, gills, and liver of these fish were analyzed during both summer and winter seasons. The Ecological Risk Index (ERI), Geo-accumulation Index (Igeo), Pollution Load Index (PLI), Estimated Daily Intake (EDI), Carcinogenic Risk (CR), and Target Hazard Quotient (THQ) were computedto evaluate the dangers to both the environment and human health. The results indicate that contamination levels differ across seasons and places, with S4 demonstrating the highest. The Igeo data reveal most sites are classified as heavily to extremely contaminated, especially for Cd and Fe. The PLI values indicate the level of pollution in some locations, particularly in winter. The Ecological danger Index (ERI) indicates a moderate to significant ecological danger for the majority of metals, with Cd presenting the greatest risk. The EDI (Estimated Daily Intake) values of heavy metals indicate potential dangers of dietary exposure, with the levels of Pb (lead) and Cd (cadmium) beyond the recommended limits. The THQ values for the majority of metals are less than 1, which suggests a low risk of non-carcinogenic health effects. Nevertheless, the CR values for Pb and Cd indicate possible carcinogenic hazards, especially at sites S3 and S4. The investigation reveals substantial heavy metal pollution in the Al-Diwaniyah River, which has important consequences for ecosystem well-being and the safety of humans. The study's limitations are due to its narrow focus on time and space, which necessitates additional research to cover wider periods and more thorough risk evaluations. Future research should additionally investigate the process of bioaccumulation and devise methods to minimize the contamination of heavy metals to protect both the environment and public health.